Carbon for nutrient exchange between arbuscular mycorrhizal fungi and wheat varies according to cultivar and changes in atmospheric carbon dioxide concentration. (23rd October 2019) - Thirkell, Tom J.; Pastok, Daria; Field, Katie J.
Abstract: Arbuscular mycorrhizal fungi (AMF) form symbioses with most crops, potentially improving their nutrient assimilation and growth. The effects of cultivar and atmospheric CO2 concentration ([CO2 ]) on wheat–AMF carbon‐for‐nutrient exchange remain critical knowledge gaps in the exploitation of AMF for future sustainable agricultural practices within the context of global climate change. We used stable and radioisotope tracers ( 15 N, 33 P, 14 C) to quantify AMF‐mediated nutrient uptake and fungal acquisition of plant carbon in three wheat ( Triticum aestivum L.) cultivars. We grew plants under current ambient (440 ppm) and projected future atmospheric CO2 concentrations (800 ppm). We found significant 15 N transfer from fungus to plant in all cultivars, and cultivar‐specific differences in total N content. There was a trend for reduced N uptake under elevated atmospheric [CO2 ]. Similarly, 33 P uptake via AMF was affected by cultivar and atmospheric [CO2 ]. Total P uptake varied significantly among wheat cultivars and was greater at the future than current atmospheric [CO2 ]. We found limited evidence of cultivar or atmospheric [CO2 ] effects on plant‐fixed carbon transfer to the mycorrhizal fungi. Our results suggest that AMF will continue to provide a route for nutrient uptake by wheat in the future, despite predicted rises in atmospheric [CO2 ]. Consideration should therefore be paid to cultivar‐specific AMF receptivity and function in the development of climate smart germplasm for the future. Abstract : Arbuscular mycorrhizal fungi (AMF) form symbioses with most crops, potentially improving their nutrient assimilation with possible applications in future sustainable agriculture. However, the effects of cultivar and increasing CO2 on wheat mycorrhizal function remain unknown. Using isotope tracers, we tracked mycorrhizal function in three wheat cultivars across two CO2 scenarios. Our results suggest AMF could provide a route of nutrient uptake to wheat in the future, despite predicted rises in atmospheric CO2 . Consideration should be paid to cultivar‐specific AMF receptivity and function in the development of climate smart future crops.